2021
DOI: 10.1108/jec-08-2021-0131
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening business incubation practices among startup firms. Evidence from Ugandan communities

Abstract: Purpose The purpose of this paper is to provide the initial evidence on the role of business incubation (BI) in supporting startups and BI practices from developing communities in Uganda. Design/methodology/approach This study is cross-sectional and a triangulation of quantitative and qualitative data were used. Data were collected by means of a questionnaire and an interview guide from 28 incubators. Findings Results indicate that business incubators play different roles in communities such as business as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Indeed, the founders team of a startup has been shown to play an important role in ensuring its success; research has demonstrated that around 65 percent of high-potential start-ups fail due to challenges within the team (Wasserman, 2013), but those who attempt to carry out their ideas as a team are more likely to succeed and be financed (Klotz et al, 2014).Therefore, the analysis depicted the main dimensions analyzed proved to be consistent with the main positions retrieved in literature. When the findings of the interviews are combined with the literature on the efficiency of incubators, it is feasible to state that, during and post-Pandemic scenario, hubs are fundamental in startup training and the development of their organizational skills and human capital (Ssekiziyivu et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the founders team of a startup has been shown to play an important role in ensuring its success; research has demonstrated that around 65 percent of high-potential start-ups fail due to challenges within the team (Wasserman, 2013), but those who attempt to carry out their ideas as a team are more likely to succeed and be financed (Klotz et al, 2014).Therefore, the analysis depicted the main dimensions analyzed proved to be consistent with the main positions retrieved in literature. When the findings of the interviews are combined with the literature on the efficiency of incubators, it is feasible to state that, during and post-Pandemic scenario, hubs are fundamental in startup training and the development of their organizational skills and human capital (Ssekiziyivu et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This methodology was adopted because it offers greater anonymity to respondents and often elicits more honest responses (Erickson and Kaplan, 2000). The approach enables researchers to describe the meaning of lived experiences of a concept or a phenomenon for several individuals (Creswell, 2013;Ssekiziyivu et al, 2023). The companies were registered and licensed by the MoWT to carry out transport business in Uganda.…”
Section: Methodsmentioning
confidence: 99%
“…For example, skills in the area of supply chain management and novel technological advancements in the business practices preparing students to embrace the entrepreneurial opportunities in the industry. This process attracts individuals to establish new startups in low-risk areas (Ssekiziyivu et al , 2021). The only thing researchers invest is their energy and effort to launch new startups.…”
Section: Literature Reviewmentioning
confidence: 99%